Nano carbides-mediated acceleration of energy release behavior of amorphous boron during ignition and combustion - Daolun Liang; Jianzhong Liu; Qili Qiu (Energy Reports, 2020)
Action mechanism of nano titanium carbide (nTiC), nano zirconium carbide (nZrC), and nano silicon carbide (nSiC) was studied using a concentrated ignition experimental system, an X-ray diffractometer and a scanning electron microscope. Each nano-carbide was mixed with B in mass ratio of 2/8 and then pressed into tablets, respectively. Furthermore, a sample of amorphous B was also prepared as the control group. All the three nano-carbides showed positive influence on the ignition of B. During the first stage of combustion, only nTiC could increase the maximum emission spectral intensity of the sample, while both nTiC and nZrC helped to increase that during the second stage of combustion. Although the addition of nano-carbides intensified the energy release rate of B (except nSiC), the expansion and diffusion of generated carbon dioxide took large amounts of heat away and reduced the surface temperature of the samples The temperature change in solid-phase exhibited a relationship with the spectral intensity change in gas-phase. The temperature increase was slow during the ignition delay stage, while the first combustion stage proceeded with rapid increase in surface temperature. The high-temperature areas regressed during the second combustion stage, accompanied by the gradual stopping of gas-phase reactions. The components and microstructure of the condensed combustion products (CCPs) were analyzed after the ignition experiment. Results showed that both nTiC and nZrC could react with B to generate corresponding metal borides, capable of promoting the ignition of B. Moreover, the catalysis of produced TiO2 and ZrO2 explain the increase of emission spectral intensity during the second combustion stage. A lot of micropores formed in the CCPs after adding nTiC, which showed a destructive effect of generated gaseous CO2 on the surface oxide layer. In general, nTiC is the top accelerant for B oxidation in this study, while nSiC is at the bottom.
Keywords: 330; Amorphous boron; Combustion temperature; Emission spectrum; Energy release behavior; Heterogeneous combustion; Nano-carbides